New Zealand journal of applied business research - University of Canterbury. College of Education; Manukau Institute of Technology (Christchurch College of Education, 2002)
The New Zealand Journal of Applied Business Research (NZJABR) publishes scholarly work with an applied value that advances business theory, research and practice. Its focus is the contemporary business environment, encompassing fields such as accounting, economics, finance, management and marketing.
Keywords: Business : Research : Methodology : Periodicals; Management : Research : Methodology : Periodicals; Affaires : Recherche : Méthodologie : Périodiques; Business : Research : Methodology; Management : Research : Methodology